2012
DOI: 10.1038/nbt.2328
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of human pluripotent stem cells into mature airway epithelia expressing functional CFTR protein

Abstract: Cystic fibrosis (CF) is a fatal genetic disease caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene that regulates chloride and water transport across all epithelia and affects multiple organs including the lungs. Here we report an in vitro directed differentiation protocol for generating functional CFTR-expressing airway epithelia from human embryonic stem cells. Carefully timed treatment by exogenous growth factors that mimic endoderm developmental pathways in vivo foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
437
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(448 citation statements)
references
References 33 publications
9
437
0
2
Order By: Relevance
“…Such an ALI is commonly used to push the maturation of human primary bronchial epithelial cells in vitro and has been used to assist in the differentiation of embryonic stem cells to lung epithelial cells (2,35,36). The ALI was maintained in media G on the basolateral side (37) and used to promote maturation and polarization of the epithelial cell layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an ALI is commonly used to push the maturation of human primary bronchial epithelial cells in vitro and has been used to assist in the differentiation of embryonic stem cells to lung epithelial cells (2,35,36). The ALI was maintained in media G on the basolateral side (37) and used to promote maturation and polarization of the epithelial cell layer.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, this differentiation requires the generation of a specialized postmitotic multiciliated cell. The differentiation of embryonic stem cells and iPSCs to airway epithelial cells has recently received increased attention (2,3). The current manuscript describes developing a differentiation protocol based upon lessons learned from embryogenesis to generate multiciliated cells (4)(5)(6)(7)(8)(9).…”
Section: Ung Disease Is the Third Highest Cause Of Death In The Unitedmentioning
confidence: 99%
“…The Cystic Fibrosis Transmembrane Regulator (CFTR) was localized to the apical membrane, as in the native airways. They next developed iPSC lines from patients with the d508 CFTR mutation from patients with CF (36). Dr. Wong demonstrated that these lines were pluripotent and could generate a functional epithelial layer.…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%
“…Members of the fibroblast growth factor family have also been linked with respiratory epithelial proliferation and differentiation, as has hepatocyte growth factor (HGF) and epidermal growth factor (46,82,83). HGF, in particular, is under investigation as a possible therapeutic agent for the treatment of pulmonary fibrosis.…”
Section: Signalling Factors In Airway Growth and Developmentmentioning
confidence: 99%
“…A controversial multipotent lung stem cell has also been claimed to exist (35). Exogenous sources of stem cells that have been proposed for use include bone marrow-derived nonhaematopoietic or mesenchymal stem cells (41)(42)(43), embryonic stem cells (ESCs) (44)(45)(46)(47), human amniotic fluid-derived stem cells (48) and induced pluripotent stem cells (49). Endogenous mesenchymal progenitors include fibroblast growth factor 10-releasing mesenchymal cells (reported in (50)), but knowledge of these cells is limited and the literature is focused on airway epithelial progenitors at present.…”
Section: Stem Cell Populations Of the Airwaysmentioning
confidence: 99%